Standardizing creative thinking scale and its relationship with team cooperation of elite league volleyball players - Fadil, Asmaa Hikmet (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to codify the scale creative thinking players Elite League B Volleyball for the year 2018 - 201 9 , as I use the descriptive survey style to fit in solving the problem of research, have been identified sample purposively, and represented my players clubs participating in the Elite League, totaling (70) A player distributed among (5) clubs, and the sample of the exploratory experiment included (14) players representing (Al- Koot Club) , As applied standard on 47 players in order to determine the validity of the scale and find a scientific basis for the measure, have been extracted grading standard and levels on the main sample amounting to 70 players, plus a sample experiment reconnaissance. we reach the following conclusions: legalization of creative thinking scale There is a clear discrepancy in the levels of players by comparing the standard scores achieved with the levels of normal distribution, and the recommendations were to use the scale of creative thinking in volleyball to determine the level of the mental capacity of the players, and to apply the scale on the players to determine the level of creative thinking for them.